Semen production performance of Frieswal bulls - TYAGI, S; MATHUR, A K; AGARWAL, S C (The Indian Journal of Animal Sciences, 2014)
SemenÂ production performance of Frieswal bulls revealed that out of 186 bulls, 173 (93.01%) ejaculated semen in artificial vagina and only 78 (45.09%) of these 173 bulls produced freezable semen, Rest of the 95 (54.91%) bulls had either very poor semen producing bulls were 41.05, 7.36 and 47.36% respectively. Four (4.21%) bulls though had satisfactory inital semen quality but had poor freezability. The overall age was 628.91 21.26 days and weight at first semen dimation 399.3+-8.13 kg in Frieswal bulls (Holstein-Friesian Sahiwal).